Evaluation of the noise level emitted by the mechanical equipment used in the construction of concrete roads in Desaguadero, Peru 2020 - Huaquisto Cáceres, Samuel (2021)
Noise pollution during the construction process of a rigid pavement is an environmental factor that negatively affects the quality of life of workers and the surrounding population, in this sense, the objective of the study was to analyze the noise levels emitted by mechanical equipment. used in the construction of urban roads in order to offer hearing protection to workers. The results indicate that the mechanical equipment used in the construction of roads in the Desaguadero district emits noise levels from 69.6±5.1 dBA to 98.4±3.8 dBA, with light equipment being the most influential. The loudest task is cutting concrete in pavement which exhibits a noise level of 87.88±3.2 dBA measured at a radius of five meters from the source. In conclusion, the mechanical equipment used in the construction of roads emits noise levels that can affect the health of the population and the performance of workers, recommending the use of hearing protectors with a minimum level NRR 15 dB for equipment operators heavy mechanical and 25 dB NRR for light equipment.